Pengaruh Kualitas Produk dan Personal Selling Terhadap Pertumbuhan Jumlah Rekening Tabungan di BPRS Bhakti Sumenkar KCP Ganding - Insiyah, Cici'; Wulandari, Dewi Eka; Sudianto, Sudianto; Supriyadi, Supriyadi (Masyrif : Jurnal Ekonomi, Bisnis dan Manajemen, 2024)
BPRS Bhakti Sumekar KCP Ganding, a regional Islamic bank owned by the Sumenep Regency Government, faces numerous challenges to maintain competitiveness and market share. To address this, the bank focuses on meeting customer needs and providing superior services. One strategy employed is offering high-quality products and optimal services, enabling Tabungan Barokah to grow and compete in the market. This study aims to investigate the impact of product quality and personal selling on the growth of Tabungan Barokah accounts at BPRS Bhakti Sumekar KCP Ganding. Using a quantitative descriptive approach, this research sampled 100 respondents from a population of 1,030 Tabungan Barokah customers in 2022, determined using Slovin's formula. Data collection techniques included questionnaires, observation, and documentation, analyzed through validity, reliability, classical assumption, T-test, and F-test. Results indicate that product quality and personal selling significantly influence the growth of Tabungan Barokah accounts, both partially and simultaneously. Personal selling emerged as the dominant variable, with a coefficient of 0.396, surpassing product quality's coefficient of 0.277.